Useful outcome measures in INPH patients evaluation - Mori, Laura; Collino, Federica; Marzi, Annalisa; Pellegrino, Lucia; Ponzano, Marta; Chiaro, Davide Del; Maestrini, Sara; Caneva, Stefano; Pardini, Matteo; Fiaschi, Pietro; Zona, Gianluigi; Trompetto, Carlo; et al. (Frontiers in Neurology, 2023)
Introduction Idiopathic normal pressure hydrocephalus (INPH) is a neurological disorder that is potentially reversible and clinically characterized by a specific triad of symptoms, including gait disturbance, cognitive disorders, and urinary incontinence. In INPH assessment, the most commonly used test is the Timed Up and Go test (TUG), but a more comprehensive assessment would be necessary. The first aim of the present study is to verify the sensitivity of a protocol with both clinical and instrumental outcome measures for gait and balance in recognizing INPH patients. The second aim is to verify the most important spatio-temporal parameters in INPH assessment and their possible correlations with clinical outcome measures. Methods Between January 2019 and June 2022, we evaluated 70 INPH subjects. We assessed balance performances with the Berg Balance Scale (BBS), Short Physical Performance Battery (SPPB), and TUG, both single (ST) and dual task (DT). We also performed an instrumental gait assessment with the GAITRite electronic walkway system, asking the patients to walk on the carpet for one minute at normal speed, fast speed, and while performing a dual task. We compared the results with those of 20 age-matched healthy subjects (HS). Results INPH patients obtained statistically significant lower scores at the BBS, SPPB, and TUG DT but not at the TUG ST, likely because the DT involves cognitive factors altered in these subjects. Concerning instrumental gait evaluation, we found significant differences between HS and INPH patients in almost all spatio-temporal parameters except cadence, which is considered a relevant factor in INPH guidelines. We also found significant correlations between balance outcome measures and gait parameters. Discussion Our results confirm the usefulness of BBS and suggest improving the assessment with SPPB. Although the TUG ST is the most commonly used test in the literature to evaluate INPH performances, it does not identify INPH; the TUG DT, instead, might be more useful. The GAITRite system is recognized as a quick and reliable tool to assess walking abilities and spatio-temporal parameters in INPH patients, and the most useful parameters are stride length, stride width, speed, and the percentage of double support. Both clinical and instrumental evaluation may be useful in recognizing subjects at risk for falls.